Listeria monocytogenes infection in nude mice. - Emmerling, P (1975)
As compared to phenotypically normal (nu/+)NMRI mice showing the typical course of an experimental listeric infection, that of congenitally hypothymic (nude, nu/nu)NMRI mice was found to be characterized from the outset bya chronic trend. During the early phase of the infection, significantly reduced numbers of Listeria monocytogenes were observed in the spleens of nude mice.